فاعلية تطبيق التعلم النقال للشعر الجاهلي لدى الطلبة الناطقين بغير العربية - Muhamad Zamri bin Abdul Gani (Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2018)
This study aims to investigate the effectiveness of mobile learning in learning Classical Arabic Poetry among student's non-native speaker. A mobile apps named “Diwanus Shi'ir” was used in this study to help to investigate the effectiveness of mobile learning in Classical Arabic Poetry. “Diwanus Shi'ir” app was developed by a team of researchers from the International Islamic University of Malaysia (IIUM) funded by the Malaysian Ministry of Higher Education (MoHE). The study was conducted using the descriptive, analytical and experimental methodologies. The participants of the study were selected using the purposive sampling method. 50 non-native speaker students from Arabic Department from International Islamic University Malaysia were chosen to participate in this study. The data collected using pre-test, post-test and questionnaire to know any significant value differences between experimental and control group and also their opinion on app “Diwanus Shi'ir”. The results confirmed that there were no significant value differences between groups after using “Diwanus Shi'ir” app. However, this study found that learning Classical Arabic Poetry through mobile learning using “Diwanus Shi'ir” has positive impact to their study. Through questionnaire, the respondents agreed that “Diwanus Shi'ir” was a new experience for them to learn Classical Arabic Poetry which would increase the students' desire, motivates them to learn Classical Arabic Poetry